Copper-silver bimetallic catalyst as well as preparation method and application thereof
By introducing Ag nanoparticles on the catalyst surface and accelerating C-C coupling using adjacent Cu2O active sites of Ag, the problems of poor stability and low selectivity in the preparation of polycarbon products during catalytic carbon dioxide reduction are solved, and the generation of polycarbon products with high selectivity and high current density is achieved.
Patent Information
- Application Number
- CN202411837323.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
Existing catalysts have problems of poor stability and low selectivity in preparing polycarbon products by catalyzing carbon dioxide reduction.
Using copper-silver bimetallic catalyst, the CO coverage is improved by introducing Ag nanoparticles on the catalyst surface, and the C-C coupling rate is accelerated through the adjacent Cu2O active sites of Ag, thereby realizing the CO2 conversion tandem reaction process.
The selectivity of C2+ products was significantly improved. When the copper-silver ratio was 1:20, the selectivity of polycarbon products was as high as 81.6% at the voltage of -1.1V vs. RHE, and the current density was 482mA cm-2.
Smart Images

Figure CN119710814A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanocatalysts, and in particular to a copper-silver bimetallic catalyst, a preparation method and application thereof. Background Art
[0002] Since the 21st century, the consumption of fossil fuels has continued to increase, resulting in large-scale carbon dioxide emissions. Excessive carbon dioxide will hinder the reflected solar energy from dissipating into outer space, thereby causing climate warming and a series of global environmental hazards. The electrochemical conversion of CO2 into liquid fuels and value-added chemicals is an effective way to alleviate the greenhouse effect caused by CO2 emissions. There are many products of CO2 electroreduction, mainly including carbon monoxide (CO), formic acid (HCOOH), methanol (CH3OH), methane (CH4), ethanol (C2H5OH), ethylene (C2H4), etc. Among them, multi-carbon products with high energy density (C2H4, C2H5OH, etc.) have excellent economic and application prospects, but there are still problems such as low selectivity of target products and poor catalyst stability.
[0003] Since the copper surface has a suitable adsorption strength for the key reaction intermediate CO, it is considered to be an excellent metal catalyst for electrocatalytic carbon dioxide reduction. The generation of multi-carbon products is based on the combination of high CO concentration on the catalyst surface and CC coupling active sites. The low CO concentration and slow CC coupling rate on the surface of pure Cu nanoparticle catalysts hinder the high selectivity of multi-carbon products. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is that the existing catalysts for catalytic reduction of carbon dioxide to prepare multi-carbon products have problems such as poor stability and low selectivity. The present invention provides a copper-silver bimetallic catalyst, a preparation method and its application, which uses Ag nanoparticles to increase the CO concentration on the catalyst surface, and the Cu2O active sites adjacent to Ag accelerate the CC coupling rate, realize the CO2 conversion cascade reaction process, and improve C 2+ Product selectivity.
[0005] To achieve the above object, the present invention provides a method for preparing a copper-silver bimetallic catalyst, comprising the following steps:
[0006] Step 1, dissolving a soluble copper salt in a solvent to obtain a precursor solution A;
[0007] Step 2, while stirring the precursor solution A, a certain amount of sodium hydroxide solution is added dropwise to obtain solution B;
[0008] Step 3, after a certain period of time, add a certain amount of ascorbic acid to solution B under stirring, and stir rapidly to obtain suspension C;
[0009] Step 4, adding a certain amount of soluble silver salt to the suspension C under stirring, and stirring for a certain period of time to obtain a suspension D;
[0010] Step 5: Collect the reaction solid in the suspension D, wash and dry the reaction solid to obtain a copper-silver bimetallic catalyst.
[0011] Further, the soluble copper salt includes one or more of copper chloride, copper sulfate, copper nitrate and acetylacetone, and the solvent includes one of deionized water, ethanol and acetone.
[0012] Furthermore, the molar ratio of sodium hydroxide to copper is 2:1 to 10:1.
[0013] Furthermore, the molar ratio of ascorbic acid to copper sulfate added in step 3 is 5:1 to 1:1.
[0014] Another preferred embodiment of the present invention provides a copper-silver bimetallic catalyst, wherein the molar ratio of silver to copper is 1:50 to 1:5.
[0015] Furthermore, it is a doped bimetallic catalyst, in which silver is used as a doping element, that is, a silver-doped Cu2O catalyst, wherein cuprous oxide has a cubic morphology and a particle size of about 40 nm; and silver is a particle with a particle size of 10 nm.
[0016] Another preferred embodiment of the present invention provides an application of a copper-silver bimetallic catalyst for electrocatalytic reduction of carbon dioxide to convert CO2 into multi-carbon products, specifically including in a gas diffusion flow electrolytic cell separated into a cathode tank and an anode tank by an ion exchange membrane, using a silver / silver chloride electrode as a reference electrode, a nickel foam as a counter electrode, and a gas diffusion electrode as a working electrode to perform constant current electrocatalytic carbon dioxide to produce multi-carbon products; using a peristaltic pump to circulate cathode / anode electrolyte;
[0017] The gas diffusion electrode is loaded with a copper-silver bimetallic catalyst, and the loading amount of the copper-silver bimetallic catalyst is 1 to 5 mg cm -2 .
[0018] Furthermore, the electrolyte is potassium hydroxide KOH, the concentration is 0.5 to 5 mol / L, and the electrolyte flow rate is 20 to 50 ppm.
[0019] Furthermore, the voltage range for the electrocatalytic carbon dioxide electrolysis test was -0.7 to -1.2 V (vs. RHE).
[0020] Furthermore, the flow rate of the carbon dioxide gas is 15-30 sccm.
[0021] Technical Effects
[0022] The invention proposes a method for preparing a copper-silver bimetallic catalyst, which uses a wet chemical synthesis method to create a series of bimetallic catalysts with different copper-silver molar ratios. With Cu2O cubes as the substrate and silver nanoparticles as the dopant, the silver nanoparticles are in close contact with the cuprous oxide interface, forming a dense CO generation and CC coupling catalytic site.
[0023] The catalyst prepared by the copper-silver bimetallic catalyst preparation method proposed in the present invention has the silver nanoparticles doped to increase the coverage of CO on the catalyst surface, and at the same time adjust the Cu2O electronic structure to change the adsorption strength of CO2 conversion intermediate species on the catalyst surface. The Cu2O active sites adjacent to Ag promote CC coupling, increase C 2+ When the copper-silver ratio is 1:20, the selectivity of multi-carbon products is as high as 81.6% at a voltage of -1.1 V vs. RHE and a current density of 482 mA cm -2 .
[0024] The invention discloses a method for preparing a copper-silver bimetallic catalyst. The synthesis method is simple and safe, and does not involve complex conditions such as special gases and high-temperature forging. No harmful substances are produced, the method has good repeatability, and is suitable for large-scale mass production. The method can accurately control the size and electronic structure of catalyst nanoparticles, which is conducive to creating dense CO generation and CC coupling reaction series catalytic active sites.
[0025] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 are X-ray diffraction spectra of copper-silver alloy catalysts of different proportions prepared in Examples 1-4 of the present invention;
[0027] Figure 2 a is a scanning tunneling electron microscope image of the copper-silver bimetallic catalyst prepared in Comparative Example 1 of the present invention;
[0028] Figure 2 b is a scanning tunneling electron microscope image of the Cu2O nano bulk catalyst prepared in Example 2 of the present invention;
[0029] Figure 3 is the distribution diagram of the electrocatalytic CO2RR reduction products of the copper-silver bimetallic catalyst prepared in Example 3 at different voltages;
[0030] Figure 4 It is the distribution diagram of the electrocatalytic CO2RR reduction products of the catalysts prepared in Example 3 and Comparative Examples 1 and 2 at different voltages. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0032] In the following description, specific details such as specific internal procedures and techniques are provided for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from obstructing the description of the present invention.
[0033] The embodiment of the present invention provides a method for preparing a copper-silver bimetallic catalyst, comprising the following steps:
[0034] Step 1: dissolving a soluble copper salt in a solvent to obtain a precursor solution A; wherein the soluble copper salt includes one or more of copper chloride, copper sulfate, copper nitrate and acetylacetone, and the solvent includes one of deionized water, ethanol and acetone.
[0035] Step 2: While stirring the precursor solution A, a certain amount of sodium hydroxide solution is added dropwise to obtain a solution B; the molar ratio of sodium hydroxide to copper is 2:1 to 10:1.
[0036] Step 3: After a certain period of time, add a certain amount of ascorbic acid to solution B under stirring, and stir rapidly to obtain suspension C; the molar ratio of the added ascorbic acid to copper sulfate is 5:1 to 1:1.
[0037] Step 4, adding a certain amount of soluble silver salt to the suspension C under stirring, and stirring for a certain period of time to obtain a suspension D;
[0038] Step 5: Collect the reaction solid in the suspension D, wash and dry the reaction solid to obtain a copper-silver bimetallic catalyst.
[0039] Another preferred embodiment of the present invention provides a copper-silver bimetallic catalyst, wherein the molar ratio of silver to copper is 1:50 to 1:5. The catalyst is a doped bimetallic catalyst, wherein silver is used as a doping element, i.e., a silver-doped Cu2O catalyst, wherein cuprous oxide is in a cubic morphology with a particle size of about 40 nm, and silver is in the form of particles with a particle size of 10 nm.
[0040] Another preferred embodiment of the present invention provides an application of a copper-silver bimetallic catalyst for electrocatalytic reduction of carbon dioxide to convert CO2 into multi-carbon products, specifically including in a gas diffusion flow electrolytic cell separated into a cathode tank and an anode tank by an ion exchange membrane, using a silver / silver chloride electrode as a reference electrode, a nickel foam as a counter electrode, and a gas diffusion electrode as a working electrode to perform constant current electrocatalytic carbon dioxide to produce multi-carbon products; using a peristaltic pump to circulate cathode / anode electrolyte;
[0041] The gas diffusion electrode is loaded with a copper-silver bimetallic catalyst, and the loading amount of the copper-silver bimetallic catalyst is 1 to 5 mg cm -2 The electrolyte is potassium hydroxide (KOH) with a concentration of 0.5 to 5 mol / L and an electrolyte flow rate of 20 to 50 ppm. The voltage range for the electrocatalytic carbon dioxide electrolysis test is -0.7 to -1.2 V (vs. RHE). The flow rate of carbon dioxide gas is 15 to 30 sccm. The loading amount of the copper-silver bimetallic catalyst on the gas diffusion electrode is 1 mg cm -2 , the size of the gas diffusion electrode is 1 cm 2 .
[0042] The following is a specific example to illustrate a copper-silver bimetallic catalyst, a preparation method and an application thereof of the present invention.
[0043] Catalyst preparation
[0044] Embodiment 1:
[0045] 0.5 mL of 1 mol L -1 NaOH solution and 0.5 mL 1 mol L -1 The copper nitrate solution was added to a 30 mL beaker containing 9 mL of deionized water and stirred vigorously for 5 min to obtain a blue copper hydroxide suspension. 27 mg of ascorbic acid was added to the beaker, and the suspension changed from blue to yellow, confirming the formation of Cu2O nanoparticles. After stirring for 30 min, 0.02 mL of 0.01 mol L -1 The suspension was brownish yellow, stirred for 30 min, and then the mixed suspension was allowed to stand, precipitated, centrifuged, and washed. The mixture was dried in a vacuum oven at 60°C for 12 h to obtain a 1% Ag / Cu2O catalyst.
[0046] Embodiment 2:
[0047] 0.5 mL of 1 mol L -1 NaOH solution and 0.5 mL 1 mol L -1The copper nitrate solution was added to a 30 mL beaker containing 9 mL of deionized water and stirred vigorously for 5 min to obtain a blue copper hydroxide suspension. 27 mg of ascorbic acid was added to the beaker, and the suspension changed from blue to yellow, confirming the formation of Cu2O nanoparticles. After stirring for 30 min, 0.06 mL of 0.01 mol L -1 The suspension was brownish yellow, stirred for 30 min, and then the mixed suspension was allowed to stand, precipitated, centrifuged, and washed. The mixture was dried in a vacuum oven at 60°C for 12 h to obtain a Ag / Cu2O catalyst with a silver content of 3%.
[0048] Embodiment 3:
[0049] 0.5 mL of 1 mol L -1 NaOH solution and 0.5 mL 1 mol L -1 The copper nitrate solution was added to a 30 mL beaker containing 9 mL of deionized water and stirred vigorously for 5 min to obtain a blue copper hydroxide suspension. 27 mg of ascorbic acid was added to the beaker, and the suspension changed from blue to yellow, confirming the formation of Cu2O nanoparticles. After stirring for 30 min, 0.1 mL of 0.01 mol L -1 The suspension was brownish yellow, stirred for 30 min, and then the mixed suspension was allowed to stand, precipitated, centrifuged, and washed. The mixture was dried in a vacuum oven at 60°C for 12 h to obtain a Ag / Cu2O catalyst with a silver content of 5%.
[0050] Embodiment 4:
[0051] 0.5 mL of 1 mol L -1 NaOH solution and 0.5 mL 1 mol L -1 The copper nitrate solution was added to a 30 mL beaker containing 9 mL of deionized water and stirred vigorously for 5 min to obtain a blue copper hydroxide suspension. 27 mg of ascorbic acid was added to the beaker, and the suspension changed from blue to yellow, confirming the formation of Cu2O nanoparticles. After stirring for 30 min, 0.2 mL of 0.01 mol L -1 The suspension was brownish yellow, stirred for 30 min, and then the mixed suspension was allowed to stand, precipitated, centrifuged, and washed. The mixture was dried in a vacuum oven at 60°C for 12 h to obtain a Ag / Cu2O catalyst with a silver content of 10%.
[0052] Comparative Example 1:
[0053] 0.5 mL of 1 mol L -1 NaOH solution and 0.5 mL 1 mol L -1The copper nitrate solution was added to a 30 mL beaker containing 9 mL of deionized water and stirred vigorously for 5 min to obtain a blue copper hydroxide suspension. 27 mg of ascorbic acid was added to the beaker and the suspension changed from blue to yellow. After stirring for 30 min, stirring was stopped, precipitation was performed, filtration was performed, centrifugation was performed, and drying was performed in a vacuum oven at 60 ° C for 12 h to obtain a Cu2O nanocatalyst.
[0054] Comparative Example 2:
[0055] Silver citrate was added to 150 mL of deionized water containing 5 g of polyvinyl pyrrolidone. Under vigorous stirring, 60 mg of ascorbic acid aqueous solution was gradually dripped into the silver citrate solution and stirred for 1 h. The obtained black solution was centrifuged to obtain Ag nanoparticles. The Ag catalyst was obtained by washing with water and ethanol alternately for three times and drying in a vacuum oven at 60 ° C for 8 h.
[0056] XRD (X-ray crystal diffraction analysis) test
[0057] X-ray diffraction test (such as Figure 1 The results show that with the increase of Ag content, the X-ray diffraction results of the catalyst are mainly dominated by the characteristic diffraction peaks of Ag and Cu2O.
[0058] SEM (Scanning Tunneling Electron Microscope) Test
[0059] The catalysts of Example 2 and Comparative Example 1 were subjected to SEM testing, and the results are as follows: Figure 2 The results show that cuprous oxide presents a highly ordered and smooth cubic structure with a particle size of about 100nm. After loading Ag nanoparticles, cuprous oxide is in close contact with silver nanoparticles, and Ag / Cu2O exhibits an obvious heterogeneous structure. Ag nanoparticles modify the corners of Cu2O, and the size of silver nanoparticles is about 10nm.
[0060] Product distribution test of electrocatalytic carbon dioxide reduction reaction
[0061] The CO2 constant current test was performed using a gas diffusion electrolytic cell with 1M KOH as the electrolyte and electrolysis at a constant current of 200mA. Figure 3 The results show that the 5% Ag / Cu2O catalyst exhibits the best selectivity for multi-carbon products.
[0062] The 5% Ag / Cu2O catalyst prepared in Example 2 was subjected to constant voltage electrolysis tests at different potentials, with the test range being -0.7 to -1.2 V (vs. RHE). The catalyst exhibited higher CO selectivity at lower potentials, and when the potential was lower than -0.9 V, the catalyst exhibited excellent multi-carbon product selectivity. The values were -0.9 V, 78.3%; -1.0 V, 79.6%; -1.1 V, 80.6%;
[0063] The results of constant potential electrolysis of catalysts in Example 2, Comparative Example 1 and Comparative Example 2 show (as shown in Figure 4 As shown in Figure 2, silver nanoparticles have excellent CO selectivity, and silver doping on the surface of Cu2O nanoparticles improves C 2+ Product selectivity. It was confirmed that Ag increased the concentration of the intermediate product CO on the catalyst surface, and further promoted CC coupling with the Cu2O nanoparticles adjacent to Ag, realizing the CO2 reduction cascade reaction mechanism.
[0064] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a copper-silver bimetallic catalyst, characterized in that: The following steps are involved: Step 1, dissolving a soluble copper salt in a solvent to obtain a precursor solution A; Step 2, while stirring the precursor solution A, a certain amount of sodium hydroxide solution is added dropwise to obtain solution B; Step 3, after a certain period of time, add a certain amount of ascorbic acid to solution B under stirring, and stir rapidly to obtain suspension C; Step 4, adding a certain amount of soluble silver salt to the suspension C under stirring, and stirring for a certain period of time to obtain a suspension D; Step 5: Collect the reaction solid in the suspension D, wash and dry the reaction solid to obtain a copper-silver bimetallic catalyst.
2. The method for preparing a copper-silver bimetallic catalyst according to claim 1, characterized in that: The soluble copper salt includes one or more of copper chloride, copper sulfate, copper nitrate and acetylacetone, and the solvent includes one of deionized water, ethanol and acetone.
3. The method for preparing a copper-silver bimetallic catalyst according to claim 1, characterized in that: The molar ratio of sodium hydroxide to copper is 2:1 to 10:
1.
4. The method for preparing a copper-silver bimetallic catalyst according to claim 1, characterized in that: The molar ratio of ascorbic acid to copper sulfate added in step 3 is 5:1 to 1:
1.
5. The catalyst prepared by the method for preparing a copper-silver bimetallic catalyst according to any one of claims 1 to 4, characterized in that: The molar ratio of silver to copper is 1:50 to 1:
5.
6. A copper-silver bimetallic catalyst as claimed in claim 5, characterized in that: It is a doped bimetallic catalyst, in which silver is used as a doping element, namely, a silver-doped Cu2O catalyst, wherein cuprous oxide is in a cubic morphology with a particle size of about 40 nm; and silver is in particles with a particle size of 10 nm.
7. An application of a copper-silver bimetallic catalyst, characterized in that: Used for electrocatalytic reduction of carbon dioxide to convert CO2 into multi-carbon products, specifically including in a gas diffusion flow electrolysis cell separated into a cathode tank and an anode tank by an ion exchange membrane, using a silver / silver chloride electrode as a reference electrode, nickel foam as a counter electrode, and a gas diffusion electrode as a working electrode to perform constant current electrocatalysis of carbon dioxide to produce multi-carbon products; using a peristaltic pump to circulate the cathode / anode electrolyte; The gas diffusion electrode is loaded with the copper-silver bimetallic catalyst, and the loading amount of the copper-silver bimetallic catalyst is 1-5 mg cm -2 .
8. The use of a copper-silver bimetallic catalyst as claimed in claim 7, characterized in that: The electrolyte is potassium hydroxide (KOH) with a concentration of 0.5 to 5 mol / L and an electrolyte flow rate of 20 to 50 ppm.
9. The use of a copper-silver bimetallic catalyst as claimed in claim 7, characterized in that: The voltage range for the electrocatalytic carbon dioxide electrolysis test was -0.7 to -1.2 V (vs. RHE).
10. The use of a copper-silver bimetallic catalyst as claimed in claim 7, characterized in that: The flow rate of the carbon dioxide gas is 15 to 30 sccm.